Primary sebaceous gland carcinoma of pinna - Agarwal Akhilesh; Gupta Souradip; Gupta Sandipan; Guha Gautam (Wolters Kluwer Medknow Publications, 2009)
Sebaceous gland carcinoma is a rare cancer most commonly seen in the meibomian glands of the eyelid. It has predilection for periocular region and is rarely found in extra ocular sites. A case of sebaceous gland carcinoma over back of left pinna is reported.